2012
DOI: 10.1007/s00277-012-1461-y
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry in myelodysplastic syndrome: analysis of diagnostic utility using maturation pattern-based and quantitative approaches

Abstract: Flow cytometry (FCM) is being increasingly evaluated for the diagnosis of myelodysplastic syndrome (MDS). We employed multiple FCM approaches to assess MDS. Five-color FCM, morphology blind, was done on bone marrow aspirates of 57 suspected MDS and 31 normal controls. Maturation pattern, quantitative FCM for low-grade MDS that awards FCM score, and expression of selected antigens on erythroid cells and CD34(+) blasts were evaluated. FCM results were correlated with clinical and laboratory workup. Patients (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…However, these protocols used a wide diversity of techniques and antibody panels. 9,11,[17][18][19][20][21] With a view to standardizing MFC in MDS, the European LeukemiaNet (ELN) working group on MDS has defined minimal prerequisites for MFC diagnosis of MDS. 21,22 These include markers of myeloid progenitors allowing detection of an abnormal expression of CD45, CD34, CD117, HLA-DR, CD13 or CD33, asynchronous expression of CD11b or CD15 and ectopic expression of CD5, CD7, CD56 or CD19.21,22 Some intracellular markers have also been assessed in MDS, such as myeloperoxidase activity 23 or, more recently, ferritin content 24 or expression of the myeloid nuclear differentiation antigen (MNDA).…”
Section: Discussionmentioning
confidence: 99%
“…However, these protocols used a wide diversity of techniques and antibody panels. 9,11,[17][18][19][20][21] With a view to standardizing MFC in MDS, the European LeukemiaNet (ELN) working group on MDS has defined minimal prerequisites for MFC diagnosis of MDS. 21,22 These include markers of myeloid progenitors allowing detection of an abnormal expression of CD45, CD34, CD117, HLA-DR, CD13 or CD33, asynchronous expression of CD11b or CD15 and ectopic expression of CD5, CD7, CD56 or CD19.21,22 Some intracellular markers have also been assessed in MDS, such as myeloperoxidase activity 23 or, more recently, ferritin content 24 or expression of the myeloid nuclear differentiation antigen (MNDA).…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Indeed, several authors have emphasized the specificity and consistency of decreased CD71 expression in MDS patients. 8,10,11 An important caveat in the quantification of erythroid precursors is the modifications induced by red blood cell (RBC) lysis. Elimination of mature non-nucleated erythroid cells is routinely performed in MFC with various reagents.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we investigated (a) CD34+ CD45weak cells which are often analyzed for diagnostic purposes using usually myeloid markers (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and (b) CD34+ NP, which represent the first maturational steps of granulocytic cells upon attainment of primary granules and which show dysplastic characteristics morphologically and phenotypically in MDS, especially as the disease risk increases (23). In particular, we investigated (a) CD34+ CD45weak cells which are often analyzed for diagnostic purposes using usually myeloid markers (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and (b) CD34+ NP, which represent the first maturational steps of granulocytic cells upon attainment of primary granules and which show dysplastic characteristics morphologically and phenotypically in MDS, especially as the disease risk increases (23).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies using MFC have demonstrated abnormalities in the expression of specific antigens such as high CD34 and CD117, as well as abnormal CD45 expression (10)(11)(12)(13)(14)(15)(16). Many studies using MFC have demonstrated abnormalities in the expression of specific antigens such as high CD34 and CD117, as well as abnormal CD45 expression (10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
See 1 more Smart Citation